2015
DOI: 10.1148/radiol.2015142884
|View full text |Cite
|
Sign up to set email alerts
|

Can Shear-Wave Elastography be Used to Discriminate Obstructive Hydronephrosis from Nonobstructive Hydronephrosis in Children?

Abstract: US SWS measurements did not enable discrimination of obstructive hydronephrosis from unobstructive hydronephrosis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The rest amount of related articles were 13 4,5,[8][9][10][11]13,14,25,[71][72][73][74] . But, pubmed search missed some articles 6,7,12,35,75 , that was mentioned in this paper (Table 1). the two adjacent tissue.…”
Section: Literature Reviewmentioning
confidence: 78%
See 1 more Smart Citation
“…The rest amount of related articles were 13 4,5,[8][9][10][11]13,14,25,[71][72][73][74] . But, pubmed search missed some articles 6,7,12,35,75 , that was mentioned in this paper (Table 1). the two adjacent tissue.…”
Section: Literature Reviewmentioning
confidence: 78%
“…Goya was reported decrement in SWV with increasing grades of VUR, while Dilman reported as elastography did not allow to disctriminate the obstructive hydronephrosis fron non-obstructive hydronephrosis 35,75 . Goya et al and Tan et al used elastography for characterization of the masses.…”
Section: Resultsmentioning
confidence: 96%
“…Dillman et al found that SWE measurements did not enable discrimination of obstructive hydronephrosis from nonobstructive hydronephrosis in children. 20 Goya et al measured higher SWE values in nondamaged kidneys, and severely damaged kidneys had the lowest SWE values. Shear wave elastography values of normal kidneys were significantly higher than those of damaged kidneys in children.…”
Section: Discussionmentioning
confidence: 96%
“…The velocities increased in high‐grade hydronephrotic kidneys, but were not helpful in differentiating kidneys with and without obstruction of the ureteropelvic junction. Dillman et al found that SWE measurements did not enable discrimination of obstructive hydronephrosis from nonobstructive hydronephrosis in children . Goya et al measured higher SWE values in nondamaged kidneys, and severely damaged kidneys had the lowest SWE values.…”
Section: Discussionmentioning
confidence: 99%
“…It is used to determine liver and splenic stiffness in patients with chronic liver disease . Stiffness values of the kidney have also been evaluated in the kidney to assess chronic renal disease, hydronephrosis, and renal masses …”
mentioning
confidence: 99%